Elaboración de un manual de buenas prácticas de manufactura (bpm) en el laboratorio académico de materia prima animal e industria cárnica de la carrera de ingeniería agroindustrial de la Universidad Técnica de Cotopaxi periodo octubre 2014- febrero 2015 - Godoy Tapia, José Eduardo (2015)
Good manufacturing practices are rules, applied mainly in food processing and medicine production, become in powerful tools, which ensure the production of safe food for the community. This work will improve the knowledge of necessaries techniques to the standardization of production process, of mortadella, chorizo, and sausage Frankfurt, made in the laboratory of raw animal material and meat industry of agroindustrial engineering. Optimizing the resources for their preparation, in order to generate a better learning, improve the competitiveness in the professional life, ensuring a safe product and strengthen the knowledge of the student community of agroindustrial engineering at the Technical University of Cotopaxi….